The History and Aesthetics of Pixel Art - Preedakorn, Auttasead (DEC Journal : Art and Design, 2024)
This article aims to study the history and aesthetics of pixel art, focusing on its role and significance in the present day, despite the advancements in technology. The research includes an examination of relevant design works and studies, along with an analysis of artworks presented at the Thailand Biennale Chiang Rai 2023 and BIENNALE ARTE 2024. The findings reveal that pixel art remains popular and holds aesthetic value, reflecting a sense of nostalgia that influences contemporary and future design.